A presença da natureza-morta na arte contemporânea - Corrêa, Milena Regina Duarte (2020)
This study investigates the presence of still life theme in contemporary art. It aims to examine how the still life in art history goes beyond the chronology of its time, and becomes recurrent in contemporary productions, seeking to recognize its persistence, motives, behaviors and revindicationsas a contemporary object. The methodological approach of research is bibliographic and iconographic, intending to develop a writing about / with / between images of different times, valuing their dissonances and potentialities. As a reference for the problematization of images and execution of concepts, comparative relations are presented between three contemporary still lifes works, and three historical images, in order to perceive how such a recursive theme manifests itself these days. Some possible reasons for the persistence of these forms are presented, what is in communication between them, and what aspects of novelty the contemporary still life exhibits. Thus, it is clear that regardless of time, still lifes keeps a matter for artists researches, but today, themselves manifests in a contesting way, problematizing already established conceptions, carrying force, crossing different times and producing meanings that mark their presence in contemporary.